Stability of a phase composition of powders on the basis of nanodiamond in physiological solutions - Boshytska, N.V.; Perecos А.О.; Gogotsi, H.G.; Levkivska А.О.; Boshytsky, K.Yu.; Uvarova, I.V.; Lesin, V.G. (Reports of the National Academy of Sciences of Ukraine, 2018)
The physicochemical stability of powders on the base of nanodiamond in physiological solutions, which are similar by chemical composition to biological media of living organisms (water, NaCl, Ringer, and Ringer–Locke), has been investigated. It is established that the stability of the investigated powders depends on the chemical composition of physiological solutions: the powders react most intensively to Ringer–Locke solution, which includes glucose. In this case, the diamond line did not changed, but a small extent of the graphitization is observed. This make them perspective for the following use in medicine.